Experimental study on dynamic interaction between pipe and rollers in deep S-lay. (1st March 2019) - Liang, Hui; Zhao, Yan; Yue, Qianjin
Abstract: Based on a substructure experiment, the pipe laying process of a deep S-lay case is reproduced in the laboratory, and the dynamic interaction between the pipeline and stinger rollers is investigated. As a key equipment component of the S-lay, a stinger is used to support the pipe weight and control the bending deformation of the overbend section. During the S-lay process, there exist a variety of strongly nonlinear mechanic behaviors, such as the contact interaction between the pipeline and rollers, plastic strain, and large pipeline deformation. Owing to these nonlinear behaviors, roller force, as the most important design loads for the S-lay, are often difficult to predict accurately during the design stage, by means of analytical or numerical methods. In contrast, model experiments are more accurate and reliable for solving this complex nonlinear mechanics problem. In this study, the static and dynamic substructure experiments of laying a 12 inch pipe into water at a depth of 3000 m are carried out with a length scale of 1:25. The experimental results indicate that the initial roller heights and amplitudes of the vessel motions have a significant effect on the distribution of roller forces, while the stinger provides sufficient length and curvatures for the deep S-lay case.